Girlboss - Amoruso, Sophia (New York, New York : Portfolio/Penguin, Putnam, 2014)
"The first thing Sophia Amoruso sold online wasnt fashion - it was a stolen book. She spent her teens hitchhiking, committing petty theft, and dumpster diving. By age twenty -two, she had resigned herself to employment, but was still broke, directionless, and checking IDs in the lobby of an art school--a job shed taken for the health insurance. It was in that lobby that Sophia decided to start selling vintage clothes on eBay. Flash forward eight years to today, and shes the Founder, CEO and Creative Director of Nasty Gal, a $100+ million online fashion retailer with over 350 employees. Sophias never been a typical CEO, or a typical anything, and shes written #GIRLBOSS for girls like her: outsiders (and insiders) seeking a unique path to success, even when that path is windy as all hell and lined with naysayers"--Provided by publisher.
Keywords: Businesswomen -- United States; Biography; Domestic Trade